Fraser syndrome: review of the literature illustrated by a historical adult case. Issue 10 (October 2020) - Bouaoud, J.; Olivetto, M.; Testelin, S.; Dakpe, S.; Bettoni, J.; Devauchelle, B.
Abstract: Fraser syndrome (cryptophthalmos–syndactyly syndrome) is a rare autosomal recessive malformation disorder. The first description of the syndrome was reported by George Fraser in 1962. Diagnosis is based on the major and minor criteria established by van Haelst et al. in 2007. Unilateral or bilateral cryptophthalmos, syndactyly, unilateral renal agenesis, and genital anomalies are the most frequent anomalies. Several maxillofacial, oro-dental, ear–nose–throat, hormonal, and anorectal disorders are reported. Cardiac malformations and musculoskeletal anomalies are uncommon. The syndrome is related to mutations in three different genes ( FRAS1, FREM2, and GRIP1 ) resulting in failure of the apoptosis program and disruption of the epithelial–mesenchymal interactions during embryonic development. Prenatal diagnosis is based on the detection of renal agenesis and laryngeal atresia, together with a family history. Most foetuses with severe anomalies are terminated or are stillborn. All patients or pregnancies with a diagnosis of Fraser syndrome should be referred to expert centres. A collaborative approach including anaesthetists, ENT specialists, maxillofacial surgeons, and geneticists is necessary for the management of this syndrome. In vivo and in vitro research models are available to better understand the underlying aetiology.